Kesan pembelajaran koperatif terhadap pencapaian Matematik dan sikap terhadap pembelajaran Matematik bagi murid berkebolehan rendah di sekolah rendah bahagian Bintulu - Hii, Soon Bee (2010)
The purpose of this research was to identify the effectiveness of using cooperative learning method towards students' achievement and attitude in learning Mathematics for low achiever primary school in Bintulu. In particular this study seeks to determine whether the low achiever can increase their achievement and attitude in learning Mathematics using the cooperative learning method. This study was a quasi-experimental, the experimental group received teaching method using cooperative learning method, while the control group received traditional lecture method. This study was conducted in a primary school in Sarawak for eight weeks. Two of the Year Five classes have participated in this study, one class for experimental group and another class for control group. A total of 79 respondents have participated, there were 39 students in experimental group (cooperative learning method) and 40 students in control group (traditional lecture method). There were pre-achievement test, post-achievement test, pre-attitude test and post-attitude test used to collect data in this study. The questions of achievement test were based on objective and subjective questions and the attitude test was based on questionnaires. Research findings analyzed using Statistical Package for Social Science (SPSS) version 12.0. Package was chosen because it is more flexible, the researchers can create various transformations of original data in addition to the advantages that statistical procedures can be used measurement variables are Likert Scale according to 4 degrees. Data were collected and analyzed by using descriptive statistics frequency percentages, mean and standard deviation. In addition, Independent-Sample T test also used to see whether there is a significant difference between the students' achievement and attitude with the cooperative learning method. The findings showed that cooperative learning method could enhance the low achiever achievement and attitude in learning Mathematics. In addition, cooperative learning method had shown the positive effects toward the performance of cognitive, social and affective for low achiever students in primary school